Interactive and Dynamic Effects of Rootstock and Rhizobiome on Scion Nutrition in Cacao Seedlings - Schmidt, Jennifer E.; DuVal, Ashley; Puig, Alina; Tempeleu, Alexandra; Crow, Taylor (Frontiers in Agronomy, 2021)
Perennial agroecosystems often seek to optimize productivity by breeding nutrient-efficient, disease-resistant rootstocks. In cacao (Theobroma cacao L.), however, rootstock selection has traditionally relied on locally available open pollinated populations with limited data on performance. Furthermore, rootstock associations with the rhizobiome, or rhizosphere microbiome, have been neglected. Better understanding of rootstock and scion effects on cacao-specific traits, particularly those involved in root-microbe interactions and nutrient acquisition, could contribute to more efficient rootstock selection and breeding. A rootstock-scion interaction study was conducted using three scion genotypes and eight rootstock populations under greenhouse conditions to better understand the relationships among rootstock and scion identities, soil fertility, and rhizobiome composition and the impacts of these factors on plant uptake of macro- and micronutrients. We show that rootstock genotype has a stronger influence than scion on nutrient uptake, bacterial and fungal diversity, and rhizobiome composition, and that the relative contributions of rootstock and scion genotype to foliar nutrient status are dynamic over time. Correlation analysis and stepwise regression revealed complex relationships of soil physicochemical parameters and the rhizobiome to plant nutrition and emphasized strong impacts of microbial diversity and composition on specific nutrients. Linear discriminant analysis effect size estimation identified rootstock-responsive taxa potentially related to plant nutrition. This study highlights the importance of considering root-associated microbial communities as a factor in cacao rootstock breeding and the need for further investigation into mechanisms underlying nutrient acquisition and microbial interactions in grafted plants.